River Culture in Nepal - Dahal, Kamala (Nepalese Culture, 2021)
Most of the world civilizations are developed in the river basins. However, we do not have too big rivers in Nepal, though Nepalese culture is closely related with water and rivers. All the sacraments from birth to the death event in Nepalese society are related with river. Rivers and ponds are the living places of Nepali gods and goddesses. Jalkanya and Jaladeviare known as the goddesses of rivers. In the same way, most of the sacred places are located at the river banks in Nepal. Varahakshetra, Bishnupaduka, Devaghat, Triveni, Muktinath and other big Tirthas lay at the riverside. Most of the people of Nepal despose their death bodies in river banks. Death sacrement is also done in the tirthas of such localities. In this way, rivers of Nepal bear the great cultural value. Most of the sacramental, religious and cultural activities are done in such centers. Religious fairs and festivals are also organized in such a places. Therefore, river is the main centre of Nepalese cultural activities and we can find the remains of ld cultural remains in river basins.